A critical appraisal of point‐of‐care coagulation testing in critically ill patients. (22nd September 2015) - Levi, M.; Hunt, B. J.
Summary: Derangement of the coagulation system is a common phenomenon in critically ill patients, who may present with severe bleeding and/or conditions associated with a prothrombotic state. Monitoring of this coagulopathy can be performed with conventional coagulation assays; however, point‐of‐care tests have become increasingly attractive, because not only do they yield a more rapid result than clinical laboratory testing, but they may also provide a more complete picture of the condition of the hemostatic system. There are many potential areas of study and applications of point‐of‐care hemostatic testing in critical care, including patients who present with massive blood loss, patients with a hypercoagulable state (such as in disseminated intravascular coagulation), and monitoring of antiplatelet treatment for acute arterial thrombosis, mostly acute coronary syndromes. However, the limitations of near‐patient hemostatic testing has not been fully appreciated, and are discussed here. The currently available evidence indicates that point‐of‐care tests may be applied to guide appropriate blood product transfusion and the use of hemostatic agents to correct the hemostatic defect or to ameliorate antithrombotic treatment. Disappointingly, however, only in cardiac surgery is there adequate evidence to show that application of near‐patient thromboelastography leads to an improvement in clinically relevant outcomes, such as reductions in bleeding‐related morbidity and mortality, and cost‐effectiveness. More research is required to validate the utility and cost‐effectiveness of near‐patient hemostatic testing in other areas, especially in traumatic bleeding and postpartum hemorrhage.